Effects of Tailored Knowledge Enhancement on Colorectal Cancer Screening Preference across Ethnic and Language Groups - Jerant, Anthony (2012)
OBJECTIVE: Tailoring to psychological constructs (e.g. self-efficacy, readiness) motivates behavior change, but whether knowledge tailoring alone changes healthcare preferences - a precursor of behavior change in some studies - is unknown. We examined this issue in secondary analyses from a randomized controlled trial of a tailored colorectal cancer (CRC) screening intervention, stratified by ethnicity/language subgroups (Hispanic/Spanish, Hispanic/English, non-Hispanic/English). METHODS: Logistic regressions compared effects of a CRC screening knowledge-tailored intervention versus a non-tailored control on preferences for specific test options (fecal occult blood or colonoscopy), in the entire sample (N = 1164) and the three ethnicity/language subgroups. RESULTS: Pre-intervention, preferences for specific tests did not differ significantly between study groups (experimental, 64.5%; control 62.6%). Post-intervention, more experimental participants (78.6%) than control participants (67.7%) preferred specific tests (P <0.001). Adjusting for pre-intervention preferences, more experimental group participants than control group participants preferred specific tests post-intervention [average marginal effect (AME) = 9.5%, 95% CI 5.3-13.6; P <0.001]. AMEs were similar across ethnicity/language subgroups. CONCLUSION: Knowledge tailoring increased preferences for specific CRC screening tests across ethnic and language groups. PRACTICE IMPLICATIONS: If the observed preference changes are found to translate into behavior changes, then knowledge tailoring alone may enhance healthy behaviors.